Utilisation of palm oil fuel ash on precast concrete waste / Siti Nuraini Aznam and Suryani Ahmad - Aznam, Siti Nuraini; Ahmad, Suryani (2023)
This study focuses on addressing the environmental and economic implications of precast concrete piles in landfills by proposing an innovative approach: the utilisation of precast concrete construction waste in conjunction with Palm Oil Fuel Ash (POFA) to create concrete paving blocks. The main objectives of this research are to assess the mechanical strength and durability of these novel paving blocks and to develop a concrete mixture that replaces Ordinary Portland Cement (OPC) with precast cement as a binder, thereby reducing CO2 emissions associated with OPC cement. Through assembling, testing, and comparison with similar existing products, the prototype of the innovated concrete mixture was examined. The findings from this study hold significant potential to produce an alternative and cost-effective building material in Malaysia, leading to reduced dependency on natural resources. Moreover, the application of POFA in pavement block manufacturing offers a promising solution for waste management challenges in both the construction and palm oil industries, highlighting its relevance in sustainable development and circular economy practices.